RESEARCH AND MANUFACTURE THE AUTOMOTIVE HEADLIGHT CONTROLL CIRCUIT USING CAN COMMUNICATION - Bui Duc Hanh; Nguyen Van Nhon; Le Vinh Son; Duong Thi Thu Hang (Journal of Applied Science and Technology, 2019)
This article presents the results of the research and manufacture of headlights control board for vehicles using CAN network combining three controlers, a main controller (master ECU) and two auxiliary controllers (ECU1, ECU2). On this board, not only using Code Vision AVR programming software to write for Atmega8 microcontroller, but also the printed circuit was designed by the Altium Designer software. In addition, it had a function of signal converter from UART to CAN through one IC MCP2551. The result was a complete headlight control unit which could be installed on vehicles without CAN network